ECOPRENEURSHIP PADA INDUSTRI PERIKANAN: BAGAIMANAKAH MANIFESTASI ECO-INNOVATION PADA FISH â€˜N BLUES ENTERPRISE? - Cut Irna Setiawati; Zidnie Ilma (Jurnal Manajemen Maranatha, 2017)
The purpose of this study is to describe the eco-innovation manifested by Fish 'n Blues (FnB) as the realization of ecopreneurship and innovation in the fishery industry in Indonesia. This research is descriptive research with qualitative method. The informants in this study consisted of the owner and FnB staff who have been in accordance with the indicators and justification of the purpose of this study, as many as 5 people. Researchers conducted in-depth interviews with employees who were in Fish 'n Blues directly to dig up the required information. In data analysis technique, the researcher is guided by data analysis in field Miles & Huberman model, consisting of data collection, data reduction, display data, conclusion drawing and verification. The result of this research shows that eco-innovation in FnB consists of six categories consisting of product care, minor product improvement, major product improvement, functional innovation, system innovation and scientific breakthrough. In practice, product care innovation is carried out in the process of selling environmentally friendly seafood products, both raw and processed products. In minor product improvement, FnB has a product line by selling raw and processed products, so it is not just the catch. Minor changes such as seaweed pilus products, tuna meatballs, pastel shells, crispy blood clams and egg blood shells. Major product improvement is a change in the function of raw tuna products commonly used as the main menu into Tuna Spread as an additional product for other food spreads such as bread and biscuits. FnB uses a cassava bag instead of a plastic bag that becomes the solution in the plastic waste problem so that the innovation is in accordance with the functional innovation dimension related to ecopreneurship. FnB uses social media for promotions and campaigns. Selection of social media than other mass media such as television and magazine is in accordance with the dimensions of innovation system because of the innovation in communicating with consumers in a more effective way. The latter category is the scientific breakthrough that is environmentally friendly invention will affect on a wide scale or against some industry or so-called scientific breakthrough. Based on the results of the analysis, unfortunately until now FnB has not had a scientific breakthrough because FnB only focuses on selling products only.Â Keywords: ecopreneurship; Eco-innovation; Fish 'n Blues; Fisheries retailers